The Prevalence of Helicobacter pylori Virulence Factors in Bhutan, Vietnam, and Myanmar Is Related to Gastric Cancer Incidence. (18th May 2015) - Trang, Tran Thi Huyen; Shiota, Seiji; Matsuda, Miyuki; Binh, Tran Thanh; Suzuki, Rumiko; Vilaichone, Ratha-korn; Mahachai, Varocha; Tshering, Lotay; Dung, Ho D. Q.; Uchida, Tomohisa; Matsunari, Osamu; Myint, Thein; et al.
Abstract : Gastric cancer is a significant health problem in Asia. Although the prevalence of Helicobacter pylori infection is similar in Bhutan, Vietnam, and Myanmar, the incidence of gastric cancer is highest in Bhutan, followed by Vietnam and Myanmar. We hypothesized that H. pylori virulence factors contribute to the differences. The status of cagA, vacA, jhp0562, and β - (1, 3)galT(jhp0563) was examined in 371 H. pylori -infected patients from Bhutan, Vietnam, and Myanmar. Each virulence factor could not explain the difference of the incidence of gastric cancer. However, the prevalence of quadruple-positive for cagA, vacA s1, vacA m1, and jhp0562 -positive/ β - (1, 3)galT -negative was significantly higher in Bhutan than in Vietnam and Myanmar and correlated with gastric cancer incidence. Moreover, gastritis-staging scores measured by histology of gastric mucosa were significantly higher in quadruple-positive strains. We suggest that the cagA, vacA s1, vacA m1, and jhp0562 -positive/ β - (1, 3)galT -negative genotype may play a role in the development of gastric cancer.